Translations of Federico García Lorca’s Poetry into Ukrainian (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
Kovalenko A. Translations of Federico García Lorca’s Poetry into Ukrainian